A hacker manifesto - Wark, McKenzie 1961- (Harvard University Press, 2004)
'A Hacker Manifesto' deftly defines the fraught territory between the ever more strident demands by drug and media companies for protection of their patents and copyrights and the pervasive popular culture of file sharing and pirating.